Tuning morphology and magnetism of magnetite nanoparticles by calix[8]arene-induced oriented aggregation. Issue 44 (9th August 2016) - Vita, Francesco; Gavilán, Helena; Rossi, Francesca; de Julián Fernández, César; Secchi, Andrea; Arduini, Arturo; Albertini, Franca; Morales, M. Puerto
Abstract : Magnetite nanoparticles were obtained by oriented aggregation exploiting the action of calix[8]arene, an organic macrocycle capable of complexing Fe. Abstract : Magnetite nanoparticles have been prepared by oriented aggregation exploiting the action of calix[8]arene, an organic macrocycle capable of complexing Fe ions, during the synthesis. Control over the degree of aggregation enables tuning of the morphology of the product, which can vary from multicore aggregated nanoparticles to nano-octahedra, with a dramatic change in the magnetic properties. Octahedral magnetite nanoparticles display ferrimagnetic behavior, which is typical of magnetite above 40 nm in size. In contrast, multicore nanostructures exhibit a narrower hysteresis loop and remarkable heating capacity under an alternating magnetic field. With the aim of producing a material useful for biomedical applications, all samples were made to be dispersible in water and biocompatible by ligand exchange with 2, 3-dimercaptosuccinic acid. Their morphology and magnetic properties were maintained after functionalization, as well as their good colloidal properties, which were characterized by dynamic light scattering.